Dielectric and thermal properties of the methacrylate polymer bearing chalcone side group - Celik, Taner; Coskun, Mehmet Fatih (Elsevier, 2018)
The 1-(1-benzofuran-2yl)-3-(4-hydroxyphenyl)propen-1-one (compound 1) from the reaction between 1-(1-benzofuran-2-yl) ethanone and 4-hydroxybenzaldehyde was firstly synthesized. And secondly, we synthesized 4-[3-(1-benzofuran-2-y1)-3-oxoprop-1-en-1-yl] phenyl chloroacetate (compound 2) as the result of the reaction between the compound 1 and chloroacetyl chloride. The monomer was prepared by the reaction of compound 2 and sodium methacrylate. The monomer was polymerized using the free radicalic polymerization method (FRP). The structure characterization of the polymer was determined utilizing H-1 C-13- NMR and FT-IR techniques. Thermal behaviour of the homopolymer was studied by measurements of TGA and DSC. For thermal decomposition kinetics of homopolymer, Flynn-Wall-Ozawa method was applied to thermogravimetry curves. The dielectric measurements were studied using the impedance analyzer technique at a frequency which varied between 100 Hz and 20 kHz Hz depending on the alternating current (AC) conductivities. The dielectric parameters such as dielectric constant and dielectric loss are changed with the temperature. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Free radical polymerization (FRP); Dielectric constant; Chalcone; Activation energy; Thermal properties